Rehabilitative intervention during and after pediatric hematopoietic stem cell transplantation: An analysis of the existing literature. Issue 11 (13th July 2016) - Rossi, Francesca; Coppo, Monica; Zucchetti, Giulia; Bazzano, Daniela; Ricci, Federica; Vassallo, Elena; Nesi, Francesca; Fagioli, Franca
Abstract: Hematopoietic stem cell transplantation is a therapeutic strategy for several oncohematological diseases. It increases survival rates but leads to a high incidence of related effects. The objective of this paper was to examine the existing literature on physical exercise interventions among pediatric HSCT recipients to explore the most often utilized rehabilitative assessment and treatment tools. Studies published from 2002 to April 1, 2015 were selected: 10 studies were included. A previous literary review has shown that rehabilitation programs have a positive impact on quality of life. Our analysis identified some significant outcome variables and shared intervention areas.